The study pace among college students before and after a student aid reform: Some Swedish results - Daniel Avdic; Marie Gartell (Institute for Labour Market Policy Evaluation (IFAU), 2011)
In 2001, the Swedish system of student aid for college students was substantially reformed; the grant-share of the total aid was increased, students were allowed to earn more without a reduction in student aid, and the repayment schedule of the loans was significantly tightened. In this paper, we examine the effects of the reform on individual study efficiency, measured as the number of credit points achieved each semester. We use all program students with a first registration at a Swedish college between 1995 and 2001 (before the reform) and estimate a linear regression model including individual fixed effects. There is a slightly positive and significant effect of the reform on the aggregate level. However, dividing the sample conditionally on the parental educational level reveals that the individual study efficiency has increased only for students from a strong academic background. In other words, the relative study efficiency has decreased for students from a weak academic background. The different results between students from different parental backgrounds appear to be related to the reallocation of time between work and studies.
Keywords: I29; 330; study efficiency; time-to-graduation; university education; student aid; Studienfinanzierung; Hochschulpolitik; Wirkungsanalyse; Schweden